The king's stilts - Seuss, Dr. (New York : Random House, 1939)
When the King's stilts are stolen and hidden, and he can no longer enjoy his play hour, the whole kingdom is threatened with destruction until a page boy bravely saves the day.
1 8 9 10 11 13 18 29 31 33 36
Keywords: Fairy tales